1979
DOI: 10.1172/jci109472
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides sensitize unresponsive fibroblasts to Escherichia coli heat-labile enterotoxin.

Abstract: A B S T R A C T Chemically transformed mouse fibroblasts did not raise their cyclic AMP level in response to Escherichia coli heat-labile enterotoxin. These fibroblasts did, however, incorporate exogenous mono-, di-, and trisialogangliosides. After the uptake of monosialoganglioside galactosyl-N-acetylgalactosaminyl-[N-acetylneuraininyl]-galactosylglucosylceramide (GM,), the cells responded to E. coli heat-labile enterotoxin. The di-and trisialogangliosides were considerably less effective. GMI, the putative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…initial experiments with crude LT were consistent with the possibility that this enterotoxin interacted with GM1 as well as with a cell surface receptor distinct from that utilized by choleragen (20,23,24,35,38,47,48,55,(248)(249)(250)(251). In further studies using ganglioside-deficient transformed fibroblasts that lack chemically detectable ganglioside GM1 (NCTC 2071), it was observed that after incubation with GM1, but not GM2 or GM3 , their sensitivity to a relatively impure LT preparation was increased; similar results were obtained with these cells using choleragen (56,60,251).…”
Section: Similarities Betwen E Coli Heat-labile Enterotoxin and Cholsupporting
confidence: 61%
“…initial experiments with crude LT were consistent with the possibility that this enterotoxin interacted with GM1 as well as with a cell surface receptor distinct from that utilized by choleragen (20,23,24,35,38,47,48,55,(248)(249)(250)(251). In further studies using ganglioside-deficient transformed fibroblasts that lack chemically detectable ganglioside GM1 (NCTC 2071), it was observed that after incubation with GM1, but not GM2 or GM3 , their sensitivity to a relatively impure LT preparation was increased; similar results were obtained with these cells using choleragen (56,60,251).…”
Section: Similarities Betwen E Coli Heat-labile Enterotoxin and Cholsupporting
confidence: 61%
“…Ganglioside GM, is the site of CT binding (9,36); LT-Ih is believed to use GM, as well as glycoproteins (31,(37)(38)(39)(40)(41)(42). LT-IIa and LT-IIb may also bind to gangliosides, but their specificities differ from those of CT and LT, in agreement with the differences in primary structure of the B subunits (17,21,22,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 76%
“…E. coli enterotoxins which are known to evoke secretion through different intracellular signal transduction pathways. Following an initial step, which is an interaction with specific G M1 ganglioside receptors on the brush border membrane of the intestinal epithelium, 15,16) LT causes activation of adenyl cyclase and accumulation of intracellular cAMP. 17,18) The increase in intracellular cAMP activates Cl Ϫ secretion most likely acting through a cAMP-dependent protein kinase (cAK).…”
Section: Discussionmentioning
confidence: 99%